PCR FINGERPRINTING OF DIVERSE GENOMES FROM BACTERIAL STRAINS USING UNIVERSAL RICE PRIMER (URP) - Kang, Hee Wan (International Journal of Biosciences and Biotechnology; Vol 6 No 1 (2018)DO - 10.24843/IJBB.2018.v06.i01.p06, 2018)
Twenty primers of 20 mer referred to universal rice primer (URP) were developed from a repetitive sequence of rice genome. URP-PCR protocol employed stringent PCR with high annealing temperature throughout the thermo-cycling reaction, giving high reproducibility. Under the PCR condition, each single URP primer produced characteristic fingerprints from diverse genomes of bacterial species. The universal application of URP-PCR was demonstrated by applying it to 24 strains from Pectobacterium carotovoum subsp . carotov orum, 41 Agrobacterium vitis strains, 3 Xanthomonas spp. 5 Pseudomonas spp, Rhizobium sp. plant pathogenic bacteria, human and animal pathogenic bacterial strains including 6 Escherichia coli , 4 Salmonella spp., 7 Mycobacterium spp and 3 Blucella abortus strains. In addition, thermophilic bacteria were randomly isolated form high temperature compost and their URP-PCR polymorphisms were characterized with genetic relatedness.  PCR approach using URP primers will be useful for studying DNA diversity of diverse prokaryotic genomes, especially at inter- and intra species levels.